Assessing the repercussions of COVID-19 pandemic on symptoms, disease management, and emotional well-being in patients with inflammatory bowel disease: a multi-site survey study. (3rd April 2022) - El-Dallal, Mohammed; Saroufim, Ariana; Systrom, Hannah; Ballou, Sarah; Farhoud, Adel; Pasam, Ravi Teja; Gadupudi, Salini Samyuktha; Osman, Karim; Chaudrey, Khadija; Cheifetz, Adam; Feuerstein, Joseph D.
Abstract: Background: Coronavirus disease 2019 (COVID-19) pandemic has created numerous challenges in provision of safe and effective care for patients with Inflammatory Bowel Disease (IBD). In this study, we surveyed patients with IBD to highlight the impact of the pandemic on their IBD symptoms, management, and well-being. Methods: A multi-site survey was administered to patients with IBD. We evaluated patient's symptoms, medications changes, seeking medical attention, eating behaviors, sleep patterns, stress, self-reported anxiety and depression. The survey also measured emotional impact of the pandemic using the validated Pandemic Emotional Impact Scale (PEIS) and resilience using the Brief Resilience Scale (BRS). Logistic, ordinal, and linear regression models were utilized to perform sensitivity analyses. Results: The response rate to the survey was 61%. Of 391 surveyed patients, 21.1% reported worsened gastrointestinal symptoms, 17.5% reported changing biologic medication infusion schedule, 18.7% reported changing medication regimen, 43.6% attended at least one telemedicine visit with their gastroenterologist, 16.5% reported a less healthy diet, 40.5% reported worsening sleep, 63.7% reported more stress, and 65.3% reported feeling more vulnerable than before the pandemic. Women and participants with self-reported anxiety and depression were more likely to have worse symptoms, psychological well-being and daily functioning. Increased PEIS scores and decreased BRS scores were associated with worse outcomes. Conclusions: COVID-19 pandemic has impacted symptoms, disease management and well-being for patient with IBD, more prominently in patients who suffer from anxiety and depression. Utilizing PEIS and BRS scores as screening tools could help better tailor outreach and follow-up to support these patients.